Understanding European Real Exchange Rates - Crucini, Mario J; Telmer, Chris I; Zachariadis, Marios (American Economic Review, 2005)
We study good-by-good deviations from the Law-of-One-Price (LOP) for over 1,800 retail goods and services between all European Union (EU) countries for the years 1975, 1980, 1985, and 1990. We find that for each of these years, after we control for differences in income and value-added tax (VAT) rates, there are roughly as many overpriced goods as there are underpriced goods between any two EU countries. We also find that good-by-good measures of cross-sectional price dispersion are negatively related to the tradeability of the good, and positively related to the share of non-traded inputs required to produce the good. We argue that these observations are consistent with a model in which retail goods are produced by combining a traded input with a non-traded input.